Odpowiedź:
5.
(7 - x)/2 = (2 +x)/4
7/2 - 1/2x = 1/2 + 1/4x
-1/2x - 1/4x = 1/2 - 7/2
-2/4x - 1/4x = 1/2 - 3 1/2
-3/4x = -3 /*(-4/3)
x = -3 * (-4/3) = 4
6.
11 - 3x = 5x - 4(2x + 1)
11 - 3x = 5x - 8x - 4
-3x + 3x = -4 - 11
0 = -15
rownanie sprzeczne
7.
(5 - x)/7 + (8 - x)/9 = 3x/11
5/7 - 1/7x + 8/9 - 1/9x = 3/11x
-1/7x - 1/9x - 3/11x = -5/7 - 8/9
-9/63x - 7/63x - 3/11x = -45/63 - 56/63
-16/63x - 3/11x = -101/63
-176/693x - 189/693x = -101/63
-365/693x = -101/63 /*(-693/365)
x = 101/63 * 693/365 = 101 * 77/365 = 7777/365 = 21 112/365
oj, nie wiem, czy dobrze zostaly zapisane dane w zadaniu
Szczegółowe wyjaśnienie: